Toxicokinetics of Chromium in Enchytraeus crypticus (Oligochaeta) - Fátima C. F. Santos; Rudo A. Verweij; Cornelis A. M. van Gestel; Mónica J. B. Amorim (Toxics, 2022)
Chromium is naturally occurring, but emission from anthropogenic sources can lead to increased soil concentrations. Information on its toxicokinetics is essential in order to understand the time needed to reach toxicity and the mechanisms of uptake/elimination. In this study the toxicokinetics of Cr(III) was evaluated using the soil standard species Enchytraeus crypticus. The animals were exposed to 180 mg Cr/kg dry soil, a sublethal concentration, in LUFA 2.2 natural soil. OECD guideline 317 was followed, with a 14-day uptake phase in spiked soil followed by a 14-day elimination in clean soil. Exposure to Cr led to fast uptake and elimination, with Ku = 0.012 kgsoil/kgorganism/day and Ke = 0.57 day−1. The bioaccumulation factor was 0.022, and DT50 for elimination was 1.2 days. The concentration of Cr reached an internal equilibrium in the animals after 10 days. Transfer to clean soil allowed body Cr concentrations to return to background levels after approximately 7 days. E. crypticus seemed able to efficiently regulate internal Cr concentrations by actively eliminating Cr (an essential element). Although Ku and Ke deviated from the values reported in other studies for other soil invertebrates, the bioaccumulation factors were similar. These findings show the importance of toxicokinetic studies in evaluating toxicity based on internal metal concentrations that can more accurately represent the bioavailable concentration.